Analysis of the Causes of Audit Delay in IDX30 Companies on the Indonesia Stock Exchange (IDX) - Shinta Amalia; Hermawan Hermawan (Publikasi Indonesia, 2024)
The publication of financial statements has been regulated by the Indonesia Stock Exchange (IDX) and is a company obligation. Although there are regulations regarding the maximum time for the publication of audited financial statements, many companies still delay submitting these financial statements. A similar situation also occurs with companies classified under the IDX30 on the Indonesia Stock Exchange (IDX). This study explores whether the sector, profitability, and profit and loss of the company influence audit delay in IDX30 companies. This study uses a quantitative approach and purposive sampling technique for sample selection. The study population includes 30 IDX30 companies listed on the Indonesia Stock Exchange from 2018-2022. The study results indicate that the sector, profit and loss, and company profitability positively influence audit delay in IDX30 companies.